Java and Bolaang Mongondow Social Relationship - Chaterina P. Doni; Dahlia Husain (Pusat Studi Pembangunan dan Pemberdayaan, 2022)
This study aims to determine the Social Relations of the Javanese and Bolang Mongondow ethnic communities. This research uses qualitative methods with a descriptive approach. Collecting data on research through direct interviews with informants. The results of this study show that the Javanese and Bolaang Mongondow ethnic communities have had a close relationship through various media such as trade, migration, and various phenomena in the community. The nature of harmony in this multi-ethnicity causes inter-ethnic life to have an open, democratic, tolerant nature, and a willingness to coexist in differences. The relationship between Javanese ethnicities and Bolaang Mongondow is a miniature that has social harmony in Indonesia from the reality of a heterogeneous society that is often hit by waves of social disintegration.